Temperature effects on laser action of Yb3+:YCa4O(BO3)3 crystal. (December 2018) - Ma, Yanjun; Li, Yuhang; Tian, Kan; Yang, Jingnan; Dou, Xiaodan; Xu, Honghao; Han, Wenjuan; Liu, Junhai
Highlights: Temperature effects on the laser performance of Yb:YCOB crystal are revealed. Emission wavelength dependence is investigated. Laser beam quality can be improved considerably with rising temperature. Abstract: An experimental investigation was carried out to study the temperature effects on the laser performance of Yb 3+ :YCa4 O(BO3 )3 crystal. It was found that the extent, to which the laser performance was affected by temperature rising, was dependent on the lasing wavelength. With the crystal temperature being raised from 1 to 50 °C, the lasing threshold increased by a factor of 1.40–1.82; whereas the rate, at which the output power dropped with rising temperature, was determined to fall in a range from 0.006 to 0.028 W/°C, for laser action producing a moderate output power of 3 W. As the crystal temperature was raised, the laser performance deteriorated in output power, efficiency, and threshold; but the laser beam quality was improved considerably.